Release of caspase-9 from mitochondria during neuronal apoptosis and cerebral ischemia - Krajewski, Stanislaw (The National Academy of Sciences, 1999)
Caspase-9 is critical for cytochrome c (cyto-c)-dependent apoptosis and normal brain development. We determined that this apical protease in the cyto-c pathway for apoptosis resides inside mitochondria in several types of cells, including cardiomyocytes and many neurons. Caspase-9 is released from isolated mitochondria on treatment with Ca(2+) or Bax, stimuli implicated in ischemic neuronal cell death that are known to induce cyto-c release from mitochondria. In neuronal cell culture models, apoptosis-inducing agents trigger translocation of caspase-9 from mitochondria to the nucleus, which is inhibitable by Bcl-2. Similarly, in an animal model of transient global cerebral ischemia, caspase-9 release from mitochondria and accumulation in nuclei was observed in hippocampal and other vulnerable neurons exhibiting early postischemic changes preceding apoptosis. Loss of mitochondrial barrier function during neuronal damage from ischemia or other insults therefore may play an important role in making certain caspases available to participate in apoptosis.